Adsorbed waste kaolin-based rubber filler as well as preparation method and application thereof
Through solid-liquid separation, precipitation, calcination and surface modification, waste kaolin is prepared to prepare efficient rubber fillers, which solves the problems of resource utilization of waste kaolin and improves the performance of rubber composite materials, and realizes the fixation of heavy metal ions and rubber fillers. Improved mechanical properties.
Patent Information
- Application Number
- CN202411118449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art fails to effectively utilize waste kaolin after adsorption, resulting in secondary contamination of heavy metal ions and its reinforcement performance in rubber fillers, and cannot be directly applied.
Waste kaolin-based rubber fillers are prepared by solid-liquid separation, precipitation, calcination and surface modification treatment. Heavy metal ions are fixed with precipitants and modifiers to form nanometal oxides, and the surfactivity and dispersion of kaolin are improved.
The resource utilization of waste kaolin has been realized, the mechanical properties and thermal stability of rubber composite materials have been improved, heavy metal ion pollution has been reduced, and new application methods for rubber fillers have been provided.
Smart Images

Figure CN119220112A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and particularly relates to an adsorbed waste kaolin-based rubber filler and a preparation method and application thereof. Background Art
[0002] With the rapid development of the economy, heavy metal ion pollution in water bodies caused by corporate production and mineral mining poses a great threat to the human living environment. Heavy metals in water are not only unable to be degraded, but also gradually accumulate in animals or humans through the food chain, causing biological poisoning.
[0003] In the face of the increasingly serious problem of heavy metal wastewater pollution, it is an effective method to use the special molecular structure and irregular crystal defects of clay minerals to adsorb heavy metal ion wastewater. Among them, kaolin, as a non-toxic and harmless natural clay mineral, has a special crystal structure that gives it strong adsorption, plasticity and ion exchange properties, making it a very effective heavy metal ion adsorbent. For example, Huang Ming used kaolin as a raw material to prepare magnetic kaolin for the adsorption of Cu 2+ and Pb 2+ The results showed that Cu 2+ and Pb 2+ The extraction rates can reach 98.2% and 99.38% respectively (Huang Ming. Preparation of magnetic kaolin and its effect on Cu 2+ and Pb 2+ Adsorption performance [D]. East China Jiaotong University, 2016.). In addition, there are also kaolin as the main base material mixed with other components for heavy metal ion adsorption. For example, patent CN107999022A discloses a geopolymer, its preparation method and application in heavy metal ion adsorption. It reacts metakaolin with an activator to prepare a geopolymer for adsorbing heavy metal ions cadmium, and the removal rate is as high as 96%; patent CN107570123A discloses a treatment agent for wastewater containing heavy metals and its preparation method, which uses kaolin as the basic adsorbent raw material, adds zeolite and pyrite to adsorb heavy metal ions in wastewater, and finally achieves the effect of efficiently removing heavy metal ions in wastewater and reducing COD.
[0004] Although kaolin performs very well in removing heavy metal ions, there is no research on the utilization of waste kaolin obtained after kaolin adsorbs heavy metal ions. If these waste kaolins are stored for a long time, they will not only occupy land space, but also cause secondary pollution of water and soil resources by heavy metal ions. Therefore, the resource utilization of waste kaolin after adsorption will help solve the above problems.
[0005] At present, kaolin is widely used in the rubber industry due to its unique crystal structure, particle size, plasticity, electrical insulation, chemical stability and many other excellent properties. However, the high surface energy of kaolin particles, hydrophilic and oleophobic surface, and easy aggregation lead to reduced reinforcement in non-polar and weakly polar rubbers. Studies have shown that by precipitating metal ions (such as Cu 2+ 、Zn 2+ It is a very effective method to prepare rubber fillers by modifying kaolin with metal oxides (such as kaolinite, etc.). Kaolin saturated with heavy metal ions can be treated with a series of treatments to form a structure with kaolin as the main body and metal oxides covering the surface. This structure increases the surface activity of kaolin, which helps to further organically modify it to prepare rubber fillers, thereby increasing the reinforcing properties of waste kaolin-based rubber fillers in rubber. Although waste kaolin contains both kaolin and metal ions, which provides the necessary material basis for the preparation of rubber fillers with modified kaolin, it is precisely because of the adsorption of heavy metal ions on its surface that the surface charge of kaolin changes, which in turn leads to an increase in the hydrophilicity of the surface of waste kaolin. Therefore, waste kaolin cannot be directly used as a rubber filler.
[0006] How to utilize the metal ions in waste kaolin and kaolin at the same time, and to achieve efficient fixation of toxic and harmful heavy metal ions, thereby improving the surface activity of the main structure of kaolin, thereby facilitating the organic modification of the surface of kaolin and improving its application in the industrialization of rubber fillers, is a technical problem to be solved. Summary of the invention
[0007] In order to solve the above technical problems, the present invention first provides a method for preparing waste kaolin-based rubber filler after adsorption.
[0008] The technical means adopted by the present invention are as follows:
[0009] A method for preparing waste kaolin-based rubber filler after adsorption, comprising the following steps:
[0010] S1. The heavy metal ion wastewater adsorbed by kaolin is subjected to solid-liquid separation to obtain solid waste residue, namely, waste kaolin, and the waste kaolin is mixed with a set amount of precipitant, and then co-grinded and dried to obtain precipitated kaolin, wherein the precipitant is any one of ammonia, urea, ammonium carbonate, and ammonium bicarbonate;
[0011] S2. calcining the precipitated kaolin at high temperature to obtain calcined kaolin;
[0012] S3. Calcined kaolin is co-grinded with a set amount of a modifier, and the grinding product is the waste kaolin-based rubber filler; the modifier is any one of a silane coupling agent, aluminate, titanate, hexamethylsilazane, sodium dodecylbenzenesulfonate, rubber accelerator NS (N-tert-butylbenzothiazolesulfonamide), rubber accelerator DZ (N-dicyclohexylbenzothiazolesulfonamide), rubber accelerator MBT (2-thiolbenzothiophene), and rubber accelerator MBTS (dibenzothiophene disulfide).
[0013] Preferably, in the heavy metal ion wastewater, the heavy metal ion is Zn 2+ , Cu 2+ Cr 6+ 、Cd 2+ , Pb 2+ 、Ni + , Mn 4+ Any one or more combinations of .
[0014] Preferably, the mass ratio of the precipitant to the waste kaolin is 0.01 to 0.5.
[0015] Preferably, the high temperature calcination temperature is 200-1000° C., the initial temperature is 30° C., the heating rate is 2-15° C. / min, and the temperature is kept for 2 hours after reaching the target temperature.
[0016] Preferably, the high temperature calcination temperature is 300-800°C, the initial temperature is 30°C, the heating rate is 5-10°C / min, and the temperature is kept for 2 hours after reaching the target temperature.
[0017] Preferably, the amount of the modifier used is 0.5-5% of the mass of the calcined kaolin.
[0018] The present invention further provides an adsorbed waste kaolin-based rubber filler, which is prepared according to the preparation method as described above.
[0019] The present invention also provides use of the rubber filler as described above in rubber products.
[0020] Preferably, the rubber is any one or more combinations of styrene-butadiene rubber, natural rubber, nitrile rubber, and EPDM rubber.
[0021] The beneficial effects of the present invention are as follows:
[0022] The invention uses waste kaolin after heavy metal ion adsorption as raw material, and prepares a new kaolin-based rubber filler through the process of solid-liquid separation-precipitation-grinding-calcination-surface modification.
[0023] After kaolin adsorbs heavy metal ions, there are certain amounts of heavy metal ions on the surface of kaolin and between the lamellae. The grinding process helps to expose the surface of kaolin. At the same time, the precipitant reacts with the exposed heavy metal ions to form precipitates on the surface of kaolin, thus maximizing the fixation of heavy metal ions.
[0024] The process of drying and calcining ensures that the precipitate on the surface of kaolin is completely formed into nano metal oxides, which have extremely high reactivity and are helpful to improve the reactivity of kaolin. However, highly active nano metal oxides are very easy to combine with hydroxyl groups to form polar surfaces, and the abundant hydroxyl groups on the surface can cause the kaolin particles to agglomerate, which not only causes the binding property of the particles to the rubber substrate to be reduced, but also causes the powder to agglomerate in the substrate to form stress concentration, thereby reducing the performance of the rubber product. In order to overcome this problem, the present invention performs surface modification treatment on the calcined kaolin, adds a modifier and grinds the calcined kaolin together, and the modifier can be grafted with the high active sites (such as nano metal oxides) on the surface of kaolin, thereby promoting the surface modification of kaolin and improving the dispersibility and filling performance of kaolin. The waste kaolin-based rubber filler prepared by solid-liquid separation-precipitation-grinding-calcining-surface modification can provide more crosslinking nodes in the vulcanized rubber composite material, thereby improving the static mechanical properties such as stretching and tearing of the rubber composite material. Metal oxides and surface modifiers help to organize the surface of kaolin, reduce particle agglomeration, improve the compatibility of fillers and rubber substrates, and enhance the thermal stability and wear resistance of composite materials.
[0025] The present invention prepares rubber fillers with waste kaolin raw materials after adsorption, reduces solid waste discharge and heavy metal ion pollution of waste kaolin, not only provides a way to recycle waste kaolin, but also provides new ideas for the development and application of rubber fillers. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a process flow chart of preparing rubber filler using waste kaolin after adsorption in the present invention;
[0027] Figure 2 These are SEM photos of waste kaolin (a in the figure) and modified kaolin (b in the figure); the particle size distribution of waste kaolin is uneven, some particles are larger, and a small number of particles are lamellar. After precipitation, surface modification and other treatments, the particle size of modified kaolin is significantly reduced, the particle distribution is uniform, and the particle size is less than 2μm, and the dispersion between particles is significantly increased.
[0028] Figure 3The cross-sectional SEM of the rubber composite material in Example 1 (a in the figure) and the cross-sectional SEM of the rubber composite material in Example 5 (b in the figure). By comparing Figure a and Figure b, it can be seen that the cross-sectional voids are reduced, the gap between the filler particles and the rubber substrate is reduced, and the bonding between the filler and the rubber substrate is significantly enhanced. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described in more detail below in conjunction with the embodiments.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.
[0031] Example 1
[0032] S1. Add 50g kaolin to 1L heavy metal ion wastewater (containing Zn 2+ The concentration is 0.01 g / L, pH = 6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0033] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.2, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0034] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 450°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0035] S3. The obtained calcined kaolin and a silane coupling agent (silicon 69) accounting for 3% by mass of the calcined kaolin are placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 hours, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK1.
[0036] Example 2
[0037] S1. Add 50g kaolin to 1L heavy metal ion wastewater (containing Zn 2+ The concentration is 0.05g / L, pH=6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0038] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.2, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0039] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 450°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0040] S3. The obtained calcined kaolin and a silane coupling agent (silicon 69) accounting for 3% by mass of the calcined kaolin are placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 hours, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK2.
[0041] Example 3
[0042] S1. Add 70g kaolin to 1L heavy metal ion wastewater (containing Zn 2+ The concentration is 0.1 g / L, pH = 6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0043] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.35, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0044] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 650°C at a heating rate of 12°C / min, and calcined for 2h to obtain calcined kaolin;
[0045] S3. The obtained calcined kaolin and titanate 201 accounting for 3% by mass of the calcined kaolin are placed together in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 h, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK3.
[0046] Example 4
[0047] S1. Add 50g kaolin to 1L heavy metal ion wastewater (containing Cu 2+ The concentration is 0.05g / L, Zn 2+ The concentration is 0.05g / L, pH=6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0048] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.2, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0049] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 450°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0050] S3. The obtained calcined kaolin and a silane coupling agent (silicon 69) accounting for 3% by mass of the calcined kaolin are placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 hours, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK4.
[0051] Example 5
[0052] S1. Add 50g kaolin to 1L heavy metal ion wastewater (containing Cu 2+ The concentration is 0.05g / L, pH=6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0053] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.2, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0054] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 450°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0055] S3. The obtained calcined kaolin and a silane coupling agent (silicon 69) accounting for 3% by mass of the calcined kaolin were placed in a planetary ball mill, and ball-milled at a speed of 500 r / min for 3 h. The waste kaolin-based rubber filler was taken out and dried, which was recorded as MK5.
[0056] Example 6
[0057] S1. Add 40g kaolin to 1L heavy metal ion wastewater (containing Cu 2+ The concentration is 0.05g / L, Zn 2+ The concentration is 0.05g / L, pH=6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0058] Adding ammonium carbonate to the obtained waste kaolin, with the ratio of ammonium carbonate to waste kaolin being 0.4, and grinding and drying to obtain precipitated kaolin;
[0059] S2. The precipitated kaolin is placed in a muffle furnace at an initial temperature of 30°C, and the temperature is raised to 580°C at a heating rate of 5°C / min, and calcined for 2h to obtain calcined kaolin;
[0060] S3. The obtained calcined kaolin and rubber accelerator NS accounting for 2% by mass of the calcined kaolin were placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 h, and then taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK6.
[0061] Example 7
[0062] S1. Add 50g kaolin to 1L heavy metal ion wastewater (containing Cr 6+ The concentration is 0.1 g / L, pH = 6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0063] Adding ammonium carbonate to the obtained waste kaolin, with the ratio of ammonium carbonate to waste kaolin being 0.4, and grinding and drying to obtain precipitated kaolin;
[0064] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 550°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0065] S3. The obtained calcined kaolin and aluminate accounting for 3% by mass of the calcined kaolin are placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 h, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK7.
[0066] Example 8
[0067] S1. Add 50g kaolin to 1L heavy metal ion wastewater (wastewater from a certain electroplating factory, in which Zn 2+ The concentration is 0.02g / L, Cu 2+ The concentration is 0.05g / L, Cr 6+ The concentration is 0.001g / L, pH=6.0) for adsorption treatment, and after the kaolin adsorption is saturated, the heavy metal ion wastewater after adsorption is separated by suction filtration, and the solid waste residue obtained by separation is waste kaolin;
[0068] Adding ammonia water to the waste kaolin obtained, with the ratio of ammonia water to waste kaolin being 0.4, and grinding and drying the waste kaolin to obtain precipitated kaolin;
[0069] S2. The precipitated kaolin was placed in a muffle furnace at an initial temperature of 30°C, and the temperature was raised to 450°C at a heating rate of 10°C / min, and calcined for 2h to obtain calcined kaolin;
[0070] S3. The obtained calcined kaolin and a silane coupling agent (silicon 69) accounting for 3% by mass of the calcined kaolin are placed in a planetary ball mill, ball-milled at a speed of 500 r / min for 3 hours, taken out and dried to obtain a waste kaolin-based rubber filler, recorded as MK8.
[0071] test
[0072] By melt blending, the waste kaolin-based fillers MK1, MK2, MK3, MK4, MK7 and MK8 prepared in the embodiment are added to styrene-butadiene rubber, and then accelerator NS, fatty acid, zinc oxide and sulfur are added in sequence (the mass ratio of styrene-butadiene rubber, accelerator NS, fatty acid, zinc oxide, waste kaolin-based filler and sulfur is 100:1:1:3:50:1.75), mixed evenly and vulcanized to obtain styrene-butadiene rubber composite materials, which are recorded as MR1, MR2, MR3, MR4, MR7 and MR8 in sequence. The mechanical properties of styrene-butadiene rubber composite materials are shown in Table 1. Among them, SBR is pure styrene-butadiene rubber without filler, and the filler added to CBR is N660 (the mass ratio of styrene-butadiene rubber to N660 is 100:50), and the other agents and processing procedures are the same as above.
[0073] Table 1 Mechanical properties of styrene-butadiene rubber composites
[0074]
[0075] From the data results in Table 1, it can be seen that the strength of pure styrene-butadiene rubber without any filler is extremely low, with a tensile strength of only 1.78Mpa and a tear strength of less than 10KN / m. 2 (9.77KN / m 2 ), the elasticity is also low, and the elongation at break is only 348%. The above data show that the actual application scope of pure styrene-butadiene rubber is very limited. After adding fillers, the tensile and tear strength of styrene-butadiene rubber are greatly improved. From the tensile strength results, it can be seen that the tensile strength of styrene-butadiene rubber composites increased by 6.51 to 11.18 times and the tear strength increased by 3.34 to 4.06 times after filling with waste kaolin-based rubber fillers. In addition, after filling with waste kaolin fillers, the hardness of styrene-butadiene rubber composites is also improved, and the elastic properties are also significantly improved. Therefore, the filling application of waste kaolin-based rubber fillers can effectively improve the mechanical properties of styrene-butadiene rubber.
[0076] After the styrene-butadiene rubber is filled with industrial product carbon black (N660), its tensile strength and tear strength are 19.97Mpa and 40.96KN / m 2 The tensile strength and tear strength of MR4 filled with waste kaolin are 19.90Mpa and 39.67KN / m respectively. 2, which is almost equivalent to the industrial product carbon black N660. However, the elongation at break of MR4 filled with waste kaolin filler is 531%, while the strength of carbon black N660 is 499%. MR4 filled with waste kaolin filler has higher elasticity and can replace carbon black N660 in rubber products with higher elasticity requirements. Therefore, the rubber filler prepared from waste kaolin not only realizes resource utilization while non-toxic and harmless solid waste, but also has the potential to replace high-energy-consuming and high-polluting carbon black products made from petrochemicals.
[0077] In addition, by comparing the results of MR1, MR2, and MR3, it can be seen that kaolin that absorbs heavy metal ions of different concentrations can be prepared into rubber fillers after being treated by this method. And as the concentration of heavy metal ions in wastewater increases, the tensile strength of rubber fillers prepared from waste kaolin continues to increase. By comparing MR4, MR7, and MR8, it can be seen that for kaolin that absorbs mixed heavy metal ions, the rubber fillers prepared by this method also have outstanding mechanical properties.
[0078] Using the same method, MK4, MK5, and MK6 were added to natural rubber (natural rubber, accelerator TMTD, fatty acid, zinc oxide, antioxidant RD, waste kaolin-based filler, and sulfur were added in a mass ratio of 100:1:2:5:1:50:2.5) to obtain natural rubber composites MR4, MR5, and MR6. The mechanical properties of the natural rubber composites are shown in Table 2.
[0079] Table 2 Mechanical properties of natural rubber composites
[0080]
[0081] From the results in Table 2, it can be seen that the rubber filler prepared from waste kaolin can be effectively added to natural rubber to improve the mechanical properties of natural rubber. For example, the tensile strength of pure natural rubber is 18.87MPa. After filling with waste kaolin-based fillers, the tensile strength increases to 21.54MPa (MR6), and the elongation at break, tensile strength and tear strength are also improved to a certain extent.
[0082] In summary, the kaolin adsorbing heavy metal ions can be prepared into rubber fillers for improving the mechanical properties of rubber composite materials after being treated by the method of the present invention. At the same time, the method has strong adaptability to the concentration of heavy metal ions and the types of heavy metal ions in the adsorbed wastewater. In addition, the rubber filler prepared by the method also has a more prominent application effect in different types of rubber. The method of the present invention has opened up new ideas for the harmless and resourceful utilization of waste kaolin adsorbing heavy metal ions.
[0083] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing waste kaolin-based rubber filler after adsorption, characterized in that: The following steps are involved: S1. The heavy metal ion wastewater adsorbed by kaolin is subjected to solid-liquid separation to obtain solid waste residue, namely, waste kaolin, and the waste kaolin is mixed with a set amount of precipitant, and then co-grinded and dried to obtain precipitated kaolin, wherein the precipitant is any one of ammonia, urea, ammonium carbonate, and ammonium bicarbonate; S2. calcining the precipitated kaolin at high temperature to obtain calcined kaolin; S3. Calcined kaolin is co-grinded with a set amount of a modifier, and the grinding product is the waste kaolin-based rubber filler; the modifier is any one of a silane coupling agent, aluminate, titanate, hexamethylsilazane, sodium dodecylbenzene sulfonate, rubber accelerator NS, rubber accelerator DZ, rubber accelerator MBT, and rubber accelerator MBTS.
2. The method for preparing the adsorbed waste kaolin-based rubber filler according to claim 1, characterized in that: In the heavy metal ion wastewater, the heavy metal ion is Zn 2+ , Cu 2+ Cr 6+ 、Cd 2+ , Pb 2+ 、Ni + , Mn 4+ Any one or more combinations of .
3. The method for preparing the adsorbed waste kaolin-based rubber filler according to claim 1, characterized in that: The mass ratio of the precipitant to the waste kaolin is 0.01 to 0.
5.
4. The method for preparing the adsorbed waste kaolin-based rubber filler according to claim 1, characterized in that: The high temperature calcination temperature is 200-1000° C., the initial temperature is 30° C., the heating rate is 2-15° C. / min, and the temperature is kept for 2 hours after reaching the target temperature.
5. The method for preparing the adsorbed waste kaolin-based rubber filler according to claim 4, characterized in that: The high temperature calcination temperature is 300-800° C., the initial temperature is 30° C., the heating rate is 5-10° C. / min, and the temperature is kept for 2 hours after reaching the target temperature.
6. The method for preparing the adsorbed waste kaolin-based rubber filler according to claim 1, characterized in that: The dosage of the modifier is 0.5-5% of the mass of the calcined kaolin.
7. A waste kaolin-based rubber filler after adsorption, which is prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the rubber filler as claimed in claim 7 in rubber products.
9. The use according to claim 8, characterized in that The rubber is any one or more combinations of styrene-butadiene rubber, natural rubber, nitrile rubber, and EPDM rubber.
Citation Information
Cited By
Heavy metal curing baking-free brick based on copper mine tailings and preparation method of heavy metal curing baking-free brick
CN120829288A
